Notes on the Agrotis colossa Boursin problem, with the description of new Agrotis species from China (Lepidoptera, Noctuidae) - Gyulai, Peter; Saldaitis, Aidas; Truuverk, Andro (Zootaxa, 2017)
The description of Agrotis colossa as sp. n. became necessary, since the original description has never been published and the manuscript was not found in the Boursin heritage. The original name and designation was accepted, however, the type material (holotype male and single allotype female) was completed with a series of males and females from the recent expeditions. The description of Agrotis rachingeri sp. n. is also given and the DNA results in case of both species. New taxa are illustrated with imagines in colour and male and female genitalia.